Treatment of Avascular Necrosis of the Proximal Pole of the Scaphoid by Arthroscopic Resection and Prosthetic Semireplacement Arthroplasty Using the Pyrocarbon Adaptive Proximal Scaphoid Implant (APSI): Long-Term Functional Outcomes - Gras, Mathilde; Wahegaonkar, Abhijeet L.; Mathoulin, Christophe (Journal of Wrist Surgery, 2012)
Fractures of the proximal pole of the scaphoid with associated avascular necrosis and nonunion are well known to be problematic. Many techniques for fixation and reconstruction of the proximal pole of the scaphoid have been reported, often with poor results. One of the newer modalities of treatment for these difficult cases is excision of the proximal pole and replacement with a pyrocarbon implant. The ovoid shape of the implant acts as a spacer and repositions itself throughout the range of motion of the wrist. The procedure can be performed arthroscopically, thus reducing the morbidity and allowing the procedure to be a day case. Satisfactory results have been reported in elderly patients, but there is a paucity of literature regarding the outcomes in younger patients. This multicenter retrospective study evaluates the clinical, radiologic, and functional outcomes in patients under the age of 65 years with a minimum follow up of 5 years. There were 14 patients with scaphoid nonunion advanced collapse (SNAC) grade I, II, or III wrists, with a mean age of 53 years and mean follow up of 8.7 years. There were improvements in all of the patient related variables including VAS pain scores (7.5 to 0.7), extension (45° to 60°), flexion (32° to 53°), and grip strength (15.8 to 34.6 kg). Complications included volar subluxation of the implant, which was acutely surgically corrected (1), volar subluxation of the implant, with persistent pain that required a four-corner fusion (2), and secondary radial styloidectomy (3). This technique is an attractive, minimally invasive alternative for nonunion and avascular necrosis resulting from fractures of the proximal pole of the scaphoid. The authors provide details of the technique, including technical suggestions for performing the procedure.
Keywords: avascular necrosis; non-union; proximal pole scaphoid; pyrocarbon implant; wrist arthroscopy